Menjadikan Bahasa sebagai Piranti Kohesi Perdamaian Zaman Digital - Ammar Zainuddin (Proceedings of Annual Conference for Muslim Scholars, 2018)
Language and society have a reciprocal relationship, both of which are interconnected in all respects. Even the identity of society can all be hidden by it, except the language. The global flow that makes information easy to access and re-reported is an integral part of today's digital age. It is regrettable if this advance in technology and information is not matched by informed human resources. It should be with this easy access, people can sort and prevent information that deserves to be disseminated or just the opposite. Although people know the quality of information, but they are increasingly preoccupied with social media as a means of chat and even enliven information that includes fact or not. From the current turmoil, the author wants to make people aware of the importance of the role of language in maintaining the harmony of society, especially in today's digital age. By knowing the nature of language for society and how Islam treats a language. So hopefully after reading this paper, the reader and especially the public audience is aware and more careful in speaking. Because the regularity of society also begins with their regularity in language.